Designing English Course Learning Material for Grand Zuri Hotel Padang Employees - Sherly Franchisca (Fakultas Sastra Universitas Ekasakti, 2020)
This research was aimed at designing English course handout for Grand Zuri Hotel Padang employees. The type of this research is Research and Development toward designing and producing handout for teaching and learning at Grand Zuri Hotel Padang. It is conducted for the employees of the hotel which participates for English class. In additon, there were 50 (fifty) employees involved in English teaching and learning process at Grand Zuri Hotel Padang and they were divided into two meeting. In fact, the result of the study shows that: (1) current analysis about teaching and learning process of Grand Zuri Hotel Padang related to several information of the previous teaching and learning process where the learners are in pre-intermediate level and a meeting last in 120 minutes, but there was no handout for the learners; (2) need analysis showed that the dominant skill needed by the learners based on the questionnaire were listening and speaking, generally the ability of the learners in English are good, and there were 19 (nineteen) topics that could be choosen by the learners; (3) in designing handout, there were 14 (fourteen) topics in the handout and there was also a syllabus of the handout, also the activity in the handout consist of the introduction about the topic, expressions, reading, paired practice, chit chatting, and worksheet; (4) to validate the handout, there were 4 (four) validators involved, General Manager of Grand Zuri Hotel Padang (Surni Yanti,S.Pd), two lecturers from Hotel Management Study Program at Universitas Negeri Padang, and experience trainer for English in otel industry. In conclusion, based on the findings, there should be attractive and easy to understand materials or handout for the employees of Grand Zuri Hotel Padang; (5) in order to know the effectifity of handout in teaching and learning there was limited try out in Grand Zuri Hotel. Based on the result of the try out, there is a conclution that the material which is prepared for the employees were needed in teaching and learning process , such as handout, which is made by easy and understandable format to be learned.